Cultural proximity: a source of trade flow resilience? - Céline Carrère; Maria Masood (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
While the significant influence of cultural proximity on bilateral trade flows has been extensively documented in the literature, its possible role in times of crisis has not yet been raised. Relying on a panel estimation of a gravity model incorporating cultural proximity parameters, we evidence the existence of a significant surge in the impact of the different components of cultural proximity during economic recession. The trade resilience among countries sharing a cultural bond is not a pure composition effect as it also appears within product categories. To understand this unexpected effect, we discuss different mechanisms that emphasize the potential mitigating influence of cultural proximity on some determinants of the trade collapse, namely the uncertainty shock, the increased moral hazard and the emergence of ethnocentric preferences.
Keywords: F10; F14; Z10; 330; Bilateral trade; cultural proximity; financial crisis; trade resilience